SISTEM PENUNJANG KEPUTUSAN PENENTUAN PENERIMA DANA BANTUAN RUMAH TIDAK LAYAK HUNI DENGAN METODE SMARTER DAN TOPSIS PADA DESA RAWAKALONG - Ardiansyah, Hendri; Junianto, Mochammad Bagoes Satria; Machfud, Syaeful (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2020)
This study aims to create a decision support system in determining recipients of routine assistance using smarter and topsis methods in Rawakalong Village. The reason for this is that in determining the recipient of routine grant funds is not on target, because a lot of prospective beneficiary data has to be processed and the many criteria used to be considered in determining the recipient of routine route assistance. The criteria calculations used are only based on estimates without using quantitative indicators that can provide clear and definite calculations. For this reason, a decision support system is needed that can be used to process prospective recipient's routine beneficiary data and calculate the criteria used as indicators to determine citizens who must take precedence to be given routine assistance. The existence of this system is expected to help the village apparatus in determining who should be prioritized to receive routine assistance. The method used for the Decision Support System in this study is the SMARTER (Simple Multi-Attribute Rating Technique Exploiting Rank Method) and the TOPSIS (Technique for Others Reference by Similarity to Ideal Solution) method. The SMARTER method is used to give weight to the 10 criteria used as indicators, and to rank alternatives based on existing criteria using the TOPSIS method.. Results obtained from this study, that the decision support system is very helpful to the village government as a decision-maker in determining the priority recipient of routine assistance in Rawakalong village.